+0  
 
0
295
2
avatar

 

(the answer has to be in positive exponents)

Guest Jul 21, 2017

Best Answer 

 #2
avatar+19653 
+2

simplify this expression?

\(\dfrac{2^{-1}a^2b^{-3}}{4a^3b^{-5}}\)

 

\(\begin{array}{|rcll|} \hline && \dfrac{2^{-1}a^2b^{-3}}{4a^3b^{-5}} \\\\ &=& \dfrac{2^{-1}a^2b^{-3}}{2^2a^3b^{-5}} \\\\ &=& \dfrac{2^{-1}}{2^2}\cdot \dfrac{a^2}{a^3} \cdot \dfrac{b^{-3}}{b^{-5}} \\\\ &=& \dfrac{1}{2^22^{1}}\cdot \dfrac{1}{a^3a^{-2}} \cdot \dfrac{b^{-3}b^{5}}{1} \\\\ &=& \dfrac{1}{2^{2+1}}\cdot \dfrac{1}{a^{3-2}} \cdot \dfrac{b^{-3+5}}{1} \\\\ &=& \dfrac{1}{2^{3}}\cdot \dfrac{1}{a^{1}} \cdot \dfrac{b^{2}}{1} \\\\ &=& \dfrac{1}{2^{3}}\cdot \dfrac{1}{a} \cdot \dfrac{b^{2}}{1} \\\\ &=& \dfrac{b^{2}}{2^{3}a} \\\\ &=& \dfrac{b^{2}}{8a} \\ \hline \end{array}\)

 

laugh

heureka  Jul 21, 2017
 #1
avatar
0

(b2) / (8a)

Guest Jul 21, 2017
 #2
avatar+19653 
+2
Best Answer

simplify this expression?

\(\dfrac{2^{-1}a^2b^{-3}}{4a^3b^{-5}}\)

 

\(\begin{array}{|rcll|} \hline && \dfrac{2^{-1}a^2b^{-3}}{4a^3b^{-5}} \\\\ &=& \dfrac{2^{-1}a^2b^{-3}}{2^2a^3b^{-5}} \\\\ &=& \dfrac{2^{-1}}{2^2}\cdot \dfrac{a^2}{a^3} \cdot \dfrac{b^{-3}}{b^{-5}} \\\\ &=& \dfrac{1}{2^22^{1}}\cdot \dfrac{1}{a^3a^{-2}} \cdot \dfrac{b^{-3}b^{5}}{1} \\\\ &=& \dfrac{1}{2^{2+1}}\cdot \dfrac{1}{a^{3-2}} \cdot \dfrac{b^{-3+5}}{1} \\\\ &=& \dfrac{1}{2^{3}}\cdot \dfrac{1}{a^{1}} \cdot \dfrac{b^{2}}{1} \\\\ &=& \dfrac{1}{2^{3}}\cdot \dfrac{1}{a} \cdot \dfrac{b^{2}}{1} \\\\ &=& \dfrac{b^{2}}{2^{3}a} \\\\ &=& \dfrac{b^{2}}{8a} \\ \hline \end{array}\)

 

laugh

heureka  Jul 21, 2017

5 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.